SAXIFRAGA EXTRACTS FOR COSMETIC OR THERAPEUTIC USE ON THE SKIN - MUTEL VINCENT; SCHNYDER BRUNO; SIMONNET XAVIER (2019)
An extract obtained from Saxifraga sp., Astrantia major, or a combination thereof and a method of treating or relieving an inflammatory-skin related condition in a subject is provided. The method comprises administering or applying a composition comprising an effective amount of an extract from Saxifraga sp., Astrantia major or a combination thereof, and a carrier, wherein the effective amount ofthe extract inhibits tumor necrosis factor alpha and Interleukine-1beta activity. The inflammation may be inflammation of the skin and the composition may be a skin preparation for external use. 提供了从虎耳草物种、大星芹、或其组合获得的提取物，和治疗或缓解受试者中炎症皮肤相关状况的方法。该方法包括施用或应用组合物，该组合物包含有效量的从虎耳草物种、大星芹、或其组合获得的提取物以及载体，其中有效量的提取物抑制肿瘤坏死因子alpha和白细胞介素-1beta的活性。炎症可以是皮肤的炎症，并且组合物可以是外用的皮肤制剂。